Missing effects of anthropogenic nutrient deposition on sentinel alpine ecosystems. (2nd May 2014) - Vinebrooke, Rolf D.; Maclennan, Megan M.; Bartrons, Mireia; Zettel, James P.
Abstract Anthropogenic nitrogen (N) deposition affects unproductive remote alpine and circumpolar ecosystems, which are often considered sentinels of global change. Human activities and forest fires can also elevate phosphorus (P) deposition, possibly compounding the ecological effects of increased N deposition given the ubiquity of nutrient co‐limitation of primary producers. Low N : P ratios coupled with evidence of NP‐limitation from bioassays led us to hypothesize that P indirectly stimulates phytoplankton by amplifying the direct positive effect of N (i.e. serial N‐limitation) in alpine ponds. We tested the hypothesis using the first replicated N × P enrichment experiment conducted at the whole‐ecosystem level, which involved 12 alpine ponds located in the low N deposition backcountry of the eastern Front Range of the Canadian Rockies. Although applications of N and P elevated ambient N and P concentrations by 2–5×, seston and plankton remained relatively unaffected in the amended ponds. However, additions of ammonium nitrate elevated the δ15N signals of both primary producers and herbivores (fairy shrimp; Anostraca), attesting to trophic transfer of N deposition to consumers. Further, in situ bioassays revealed that grazing by high ambient densities of fairy shrimp together with potential competition from algae lining the pond bottoms suppressed the otherwise serially N‐limited response by phytoplankton. Our findings highlight how indirect effects of biotic interactions rather the often implicit direct effects of chemical changes can regulate the sensitivities of extreme ecosystems to nutrient deposition.